An Amish healing & Ollie's story [large type] - Wiseman, Beth, 1962- (Thorndike Press large print Christian fiction series., 2025)
"Ada Glick enjoys her role as resident veterinarian in her small Amish community. Even though true love hasn't found her yet, Ada occupies her time by caring for her neighbors' fur-babies after receiving informal training from a veterinarian in town. When an injured dog shows up unexpectedly on her front porch, Ada tends to him with the care she's always given to animals in need. During the time she cares for the dog, Ada becomes attached to her furry new friend. Ollie--as she names him--doesn't have a collar and isn't well enough to travel, however she knows she must take him to be checked for an identification chip. Is there an owner who is missing him? Jeremiah Huyard has suffered a terrible loss. His family is grieving the deaths of two loved ones, a tragedy that has Jeremiah roiling in grief. When he sets eyes on the beautiful Ada at his relatives' funerals, he is unexpectedly distracted, but he is also sure he will never see her again. Can a misplaced dog and a miracle lead Ada and Jeremiah onto the path that God has laid out for them?" --